Handmade series direct-current motor - Pedrosa, Delfim Duarte Rolo (2006)
Using common materials, it is possible to build a variety of very simple - and yet functioning - electric devices. These devices can be used to verify Electromagnetism fundamentals. Electric currents within magnetic fields originate forces and that is the basic principle of operation of electric motors. This paper describes a universal series motor made with iron bars, insulated copper wire, two small brass plates, insulating tape, six screws and a couple of hoops. The motor is fed with a personal computer 12V DC switched power supply. Rotor speed can achieve several rotations per second.